SYNECOLOGICAL ANALYSIS OF HUMAN’S MICROBIOTA AS THEORETICAL PREREQUISITES OF PROBIOTICAL THERAPY - I. V. Solovyeva (Sankt-Peterburg : NIIÈM imeni Pastera, 2015)
The research results database of microflora of the large intestine of 3268 «sick» and «healthy» people of all ages is analyzed. New knowledge about the formation of human microbiota is obtained, age-specific qualitative and quantitative composition of microflora of «healthy», «sick» people and infant. These data can be prerequisites for creation of probiotics.